WADA Time to Choose a Side: Reforming the Anti-Doping Policies in U.S. Sports Leagues While Preserving Players’ Rights to Collectively Bargain - Chu, Warren (The Columbia Journal of Law & the Arts, 2021)
If you were to ask any sports fan whether performance enhancing drugs (“PEDs”) are prevalent in any of the major U.S. sports leagues, the answer would likely be a resounding “yes.” From Barry Bonds to Lance Armstrong, the specter of doping has hung over American sports for decades, and there has been consistent pressure to ramp up efforts to both deter and catch offenders. Yet, while the major U.S. sports leagues—such as Major League Baseball (MLB), the National Basketball Association (NBA), and the National Football League (NFL)—have updated their drug policies, they have not signed on to the World Anti-Doping Agency’s AntiDoping Code. To outside observers, the question arises: If American sports leagues are truly serious about catching athletes who use PEDs, then why not sign on to join the world’s largest anti-doping agency? The International Olympic Committee established the World Anti-Doping Agency (WADA) in 1999, in response to the drug scandal that occurred at the 1998 Tour de France. The Agency’s Anti-Doping Code (the “WADA Code” or the “Code”) is designed to be extremely strict and punitive in order to properly deter athletes from doping and affecting the fairness of competitions. The Code has drawn the ire of many athletes and has implicated privacy concerns, but remains in place, governing the Olympics, international sporting competitions, and even the Ultimate Fighting Championship. MLB, the NBA, and the NFL, despite past pressure from Congress and WADA officials, have continued to monitor their own athletes and collectively bargain with their players’ unions to develop drug testing policies that walk a fine line between ensuring effectiveness while minimizing invasiveness. Collective bargaining has been seen as a weakness among proponents of the WADA Code. Proponents argue that collective bargaining fails to address the players’ incentives to negotiate toothless drug policies and the leagues’ incentives to ensure that their star players are not implicated in any scandals. However, these concerns from WADA officials and the American public are overblown. This Note argues that while U.S. sports leagues have some work to do in order to properly combat doping, the WADA Code is far too draconian and overly punitive to be implemented in American sports. As they stand, the U.S. sports leagues’ policies are largely sufficient and should not become any more punitive than they currently are. However, the conflicts of interest involved when leagues and unions develop their own anti-doping policies should be addressed; specifically, the creation of these policies should be entrusted to an independent agency to ensure their unbiased development and implementation. Part I examines the WADA Code, as well as the current anti-doping policies of the NBA, the NFL, and MLB. Part II argues that the major U.S. sports leagues would be ill-advised to adopt the WADA Code to govern themselves because the WADA Code includes significant drawbacks that place unacceptable burdens on athletes’ privacy and autonomy, the difference in effectiveness is not significant enough justify the imposition of WADA’s restrictions, and doping is not a significant enough problem overall to justify WADA’s many drawbacks. Part III suggests that striking a balance between current U.S. sports league policies and the WADA Code by establishing an independent agency that liaises with each sport’s players’ union and enlists sponsors in the fight against doping. This solution would serve to address some of the issues levied at MLB, the NBA, and the NFL while avoiding the overly punitive and invasive aspects of the WADA Code.